Peculiarities of cytolytic syndrome development with associated injury of the abdominal organs and massive blood loss in the experiment - I. V. Kuzminskyi; V. K. Grodetskyi; H. Yu. Thymbalyuk (Kazimierz Wielki University, 2021)
The function of the organs responsible for detoxification processes, in particular the liver, deserves a special role in the conditions of combined trauma. It is proved that ischemia-reperfusion of the limb caused by the imposition of a tourniquet, is the cause of significant toxemia. Under such conditions, it becomes clear that the detoxification function may be impaired, especially against the background of blunt combined trauma to the abdominal organs complicated by massive bleeding. Changes in the detoxification function of the liver are indicated by markers of the cytolytic syndrome. However, there is no clear understanding of how ischemia - limb reperfusion affects the development of cytolytic syndrome. Objective of research: to study the effect of massive blood loss associated with ischemia-reperfusion of the limb on the cytolytic syndrome indicators in case of injury of the abdominal organs.   Materials and methods. 100 mature albino male Wistar rats with the body weight of 190-220 grams kept on standard vivarium forage were used in the experiment.  The animals were divided into the control and 3 research groups (containing 10 animals each). Arresting bleeding tourniquet was applied proximally on the lower limbs of rats from the first research group for 120 minutes under thiopental-sodium anesthesia (40 mg/kg-1), which caused development of ischemic-reperfusion.  Closed abdominal injury was simulated by means of delivering two dosed blows in the region of the abdominal cavity in the second research group; massive blood loss was simulated by means of cutting the femoral vessels and bloodletting from 25 to 30 % of the circulating blood volume in the group. Injuries from the first two groups were combined in the third group. The control group of animals received anesthesia without formation of any injuries. With the aim to determine alterations of cytolytic syndrome the activity of enzymes - markers of cytolytic syndrome ALT and AST were determined by means of a unified method.   The animals of the research groups were removed from the experiment under thiopental-sodium anesthesia by means of the total bloodletting from the heart. Results. Analysis of the results of the study found that cytolytic syndrome develops irrespective of the kind of injuries simulated. Thus, even during a day of post-traumatic period ALT and AST activity increases which is clearly registered in all the three research groups. Further destruction of cellular membranes increases till the 3rd day, which is manifested by a considerable increase of ALT and AST activity in the blood serum. This process continues till the 7th day. A tendency to ALT and AST decrease is observed only in the 1st group on the 7th day. Comparison of the 2nd and 3rd research groups within the time interval enables to understand that application of tourniquets on the limbs of animals with closed abdominal injury and massive bleeding deteriorates cytolytic processes. Conclusions: Simulated injuries in the research groups were associated with the occurrence of cytolytic processes possessing a tendency to develop in the period of early signs of traumatic disease.  Ischemic-reperfusion syndrome of the limbs accelerates considerably the development of systemic changes with abdominal injuries and hypovolemic shock, which was manifested by a considerable increase of ALT and AST parameters in the group with abdominal trauma and massive blood loss and becoming higher than that of the control in end of the experiment.